Wujud Ungkapan Pesona Lingkungan Hidup pada Majalah Tempo Edisi Khusus Cerita dari Laut 16-22 November 2015: Kajian Struktur Teks dan Implikasinya terhadap Pembelajaran Bahasa Indonesia Kelas X - Sulastri, Depi Endang, Dra. Atiqa Sabardila, M. Hum (2017)
This study aims to (1) describe the feature structure of discourse "Hikayat from Tepi Laut" Tempo magazine Special Edition Story from Sea 16-22 November 2015, (2) identify the form of expression of environmental enchantment on Tempo magazine special edition Story from the Sea 16-22 November 2015, and (3) describes the implications of the expression of environmental charm and the structure of Hikayat discourse text from the Edge of the Sea on Tempo magazine special edition Stories from the Sea of 16-22 November 2015 to the study of the text of the observation report of Class X. The data in this study is a phrases, sentences or paragraphs that contain the expression of environmental charm. This research data source is taken from discours wacana "Hikayat dari Tepi Laut" Tempo Special Edition Stories from the Sea 16-22 November 2015. The data collection using the method refer to the technique of record. Data analysis using the method of agih and method of padan as well as method of content analysis. The feature structure uses a chronological pyramid or a balanced vessel consisting of a title, opening or intro, body and cover. Expression of environmental enchantment can be divided into 3 things. (1) The style of language includes personification, metaphors, and litotes. (2) Lexical markers include repetition, hyponimi, synonymy, and antonymy. (3) Shaped idioms consisting of full idioms and partial idioms.. This research is also implicated to the learning of Indonesian language, especially producing the text of observation report of class X.